Linear Growth and Fat and Lean Tissue Gain during Childhood: Associations with Cardiometabolic and Cognitive Outcomes in Adolescent Indian Children. - Ghattu V Krishnaveni; Sargoor R Veena; Krishnamachari Srinivasan; Clive Osmond; Caroline H D Fall (PLoS ONE)
Background We aimed to determine how linear growth and fat and lean tissue gain during discrete age periods from birth to adolescence are related to adolescent cardiometabolic risk factors and cognitive ability. Methods Adolescents born to mothers with normal glucose tolerance during pregnancy from an Indian birth cohort (N = 486, age 13.5 years) had detailed anthropometry and measurements of body fat (fat%), fasting plasma glucose, insulin and lipid concentrations, blood pressure and cognitive function. Insulin resistance (HOMA-IR) was calculated. These outcomes were examined in relation to birth measurements and statistically independent measures (conditional SD scores) representing linear growth, and fat and lean tissue gain during birth-1, 1-2, 2-5, 5-9.5 and 9.5-13.5 years in 414 of the children with measurements at all these ages. Results Birth length and linear growth at all ages were positively associated with current height. Fat gain, particularly during 5-9.5 years was positively associated with fat% at 13.5 years (0.44 SD per SD [99.9% confidence interval: 0.29,0.58]). Greater fat gain during mid-late childhood was associated with higher systolic blood pressure (5-9.5 years: 0.23 SD per SD [0.07,0.40]) and HOMA-IR (5-9.5 years: 0.24 [0.08,0.40], 9.5-13.5 years: 0.22 [0.06,0.38]). Greater infant growth (up to age 2 years) in linear, fat or lean components was unrelated to cardiometabolic risk factors or cognitive function. Conclusion This study suggests that factors that increase linear, fat and lean growth in infancy have no adverse cardiometabolic effects in this population. Factors that increase fat gain in mid-late childhood may increase cardiometabolic risk, without any benefit to cognitive abilities.